Neuroendocrine effects of the duper mutation in Syrian hamsters: a role for Cryptochrome 1 - Manoogian, Emily N. C.; Bahiru, Michael Seifu; Wang, Emily Jue; Holder, Mary; Bittman, Eric L. (Frontiers in Physiology, 2024)
Molecular and physiological determinants of the timing of reproductive events, including the pre-ovulatory LH surge and seasonal fluctuations in fertility, are incompletely understood.We used the Cryptochrome 1-deficient duper mutant to examine the role of this core circadian clock gene in Syrian hamsters. We find that the phase of the LH surge and its stability upon shifts of the light:dark cycle are altered in duper mutants. The intensity of immunoreactive PER1 in GnRH cells of the preoptic area peaks earlier in the day in duper than wild type hamsters. We note that GnRH fibers coursing through the suprachiasmatic nucleus (SCN) contact vasopressin-and VIP-immunoreactive cells, suggesting a possible locus of circadian control of the LH surge. Unlike wild types, duper hamsters do not regress their gonads within 8 weeks of constant darkness, despite evidence of melatonin secretion during the subjective night. In light of the finding that the duper allele is a stop codon in Cryptochrome 1, our results suggest important neuroendocrine functions of this core circadian clock gene.